E-leadership drives employee creativity through emotional exhaustion with regulatory focus as a moderator - Liang Zhao; Hao Chen; Yichao Sun; Maya Luo; Peng Gao (Scientific Reports)
Abstract In the digital age, e-leadership has emerged as a critical driver of employee creativity, yet the underlying mechanisms and boundary conditions remain underexplored. This study aimed to elucidate the relationship between E-leadership and employee creativity by examining the mediating role of emotional exhaustion and the moderating influences of promotion and prevention regulatory foci. Data were collected via a questionnaire survey administered to 366 employees within China's Information and Communication Technology (ICT) sector, and the data were analyzed using hierarchical regression and bootstrapping techniques. Results demonstrate that E-leadership influences creativity through multiple concurrent pathways: a direct positive effect (β = 0.28, p 0.01, accounting for 66.7% of total effect) and an indirect effect mediated through reduced emotional exhaustion (β = 0.14, 95% CI [0.08, 0.21], representing 33.3% of total effect). These relationships are significantly moderated by regulatory focus, with promotion focus attenuating the negative association between E-leadership and emotional exhaustion (interaction β = 0.14, p = 0.01) and prevention focus exacerbating the detrimental impact of emotional exhaustion on creativity (interaction β = –0.20, p 0.01). These findings advance leadership theory by revealing how cognitive-motivational factors shape e-leadership effectiveness, with practical implications for mitigating burnout in technology-mediated work environments.